2011
DOI: 10.3354/dao02358
|View full text |Cite
|
Sign up to set email alerts
|

Rainbow trout Oncorhynchus mykiss ladderlectin, but not intelectin, binds viral hemorrhagic septicemia virus IVb

Abstract: The innate immune system of fish is critical for rapid detection and immediate response to infection, as well as to orchestrate the adaptive branch of the immune system. Rainbow trout Oncorhynchus mykiss ladderlectin and intelectin are plasma pattern recognition receptors (PRR) for bacterial and fungal pathogens of rainbow trout, but their role as PRRs for virus is unknown. Viral hemorrhagic septicemia virus (VHSV) IVb is a recently described fish pathogen in the Great Lakes, and rainbow trout can be experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 35 publications
(70 reference statements)
0
5
0
Order By: Relevance
“…Streptococcosis is an important disease, and the outbreaks affect the advancement of tilapia aquaculture globally. Also, we found the Ladderlectin gene, which has been associated with an innate immune response mechanism, that corresponds to plasma pattern recognition for bacterial, fungal and viruses in rainbow trout 66 .…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Streptococcosis is an important disease, and the outbreaks affect the advancement of tilapia aquaculture globally. Also, we found the Ladderlectin gene, which has been associated with an innate immune response mechanism, that corresponds to plasma pattern recognition for bacterial, fungal and viruses in rainbow trout 66 .…”
Section: Discussionmentioning
confidence: 76%
“…Streptococcosis is an important disease, and the outbreaks affect the advancement of tilapia aquaculture globally. Also, we found the Ladderlectin gene, which has been associated with an innate immune response mechanism, that corresponds to plasma pattern recognition for bacterial, fungal and viruses in rainbow trout 66 . www.nature.com/scientificreports/ Through captivity, fish populations present changes in behavior-related traits as well, including aggressiveness, foraging, anti-predator and reproductive behavior, which frequently decrease in complexity 36 .…”
Section: Signatures Of Selectionmentioning
confidence: 76%
“…The up-regulation of tight junction proteins (connexin, 1•6-fold) indicates improved cell-cell communication of salmon fed krill-supplemented diets, and Willebrords et al (58) reported involvement of connexin hemichannels in non-alcoholic steatohepatitis. Among genes shown to have a role in immune surveillance of KM was up-regulation of ladderlectin (three genes, 1•5-1•8 fold) with broad pathogen recognition in rainbow trout (59)(60)(61) . In addition to liver, dietary krill meal inclusion appeared to improve gut health as ectopic epithelial cells and focal Ca deposits were not observed in KM.…”
mentioning
confidence: 99%
“…Ladderlectin in rainbow trout ( O . mykiss ) has been shown to be involved in the immune response for bacterial and fungal pathogens (Reid et al, 2011). In addition, the FLK, FST, and SFST test identified regions on Chr10, Chr12, Chr13, Chr14, and Chr17 (Figure Sa,b,d).…”
Section: Resultsmentioning
confidence: 99%
“…A custom set of scripts were used to merge chromosome and scaffold level genepop files into one (https://github.com/esnie lsen/MSc-bioin forma tics). An R script (Ravinet, 2014) was used to convert the genepop file to a BayeScan input file. BayeScan was run using the SNP matrix option and a prior odds of 100.…”
Section: Identifying Genomic Regions Under Selectionmentioning
confidence: 99%